The Extent to which Public School’s Principals’ in the Directorate of Ramallah and Al-Bireh Practice and Manage Change within a Conversational Culture from the Teachers’ Point of View - Marbou, Sahar Said; Rummaneh, Nabil Suleiman (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the extent to which public school principals in the Directorate of Ramallah and Al-Bireh practice and manage change in the light of a conversational culture from the point of view of teachers. The researchers used the analytical descriptive approach, and a questionnaire was prepared of (70) statements distributed on two axes, and (8) domains were applied to a sample of (103) male and female teachers, who were selected using the random stratified method. The dialogue from the teachers’ point of view got an overall average of (3.71 out of 5), that is, with a high degree. At the domain level; The field of participation in decision-making received the highest average (3.76), then team leadership (3.71), thirdly meeting management (3.69), fourth negotiation management (3.67), all with a (significant) degree, (big). At the level of domains, communication got the highest average (3.76), then assessment of the situation (3.73), third negotiation and persuasion (3.72), fourth trust (3.70), all of them with a (significant) degree. The results also showed that there were no statistically significant differences between the teachers’ viewpoints due to the variables (gender, educational qualification, and years of service). A set of recommendations and proposals are submitted by the researchers based on the results.